Analisis Total Productive Maintenance (TPM) dengan Metode Overall Equipment Effectiveness (OEE) pada Mesin Ekstrusi di PT. Polymindo Permata - Agus Syahabuddin; Muhammad Yusuf; Marjuki Zulziar (Universitas Pamulang, 2023)
The smooth running of a system or a production process requires support from several aspects, including machine maintenance and machine availability in the production system. Maintenance includes the efforts made to ensure the machine works well, effectively, efficiently, economically, functionally and optimally. Therefore we need a good maintenance management in order to support maintenance activities, this study aims to determine the effectiveness and the biggest problem that causes downtime on the extrusion machine. The steps taken to implement it are measuring Overall Equipment Effectiveness (OEE) and knowing the biggest factors that affect the calculation of the six big losses. The world class productivity standard formulated by the Japan Institute of Plant Maintenance (JIPM), is 85%. The results of the current OEE measurement show that the productivity of the extrusion machine is 76.18%. This value indicates that it does not reach the worldclass standard value.